In silico modeling, formulation, optimization, and in-vitro evaluation of candidone microsponges for the management of colorectal cancer - Neha Yadav, Rohitas Deshmukh (Journal of Applied Pharmaceutical Science, 2024)
Cancer is one of the most lethal diseases of the twenty-first century. The present research aimed to screen out natural bioactive with the help of bioinformatics tools. The screened molecule (Candidone) was formulated as a microsponge and evaluated for the effective and safe treatment of colorectal cancer (CRC). The Microsponges were developed using Eudragit RS 100, a pH-sensitive polymer using the quasi-emulsion solvent diffusion method. A total of 9 batch formulations were prepared using 32 full factorial designs. The prepared microsponges were evaluated by various parameters such as particle size (PS), entrapment efficiency (EE), and drug release study, optimization was done by the design of an expert, which was further subjected to statistical analysis that was kinetic release mechanism, compatibility studies were performed such as fourier transform infrared spectroscopy. Using factorial design 32 for the maximum possible formulation, the optimized formulation was found to be F7 in terms of better release for a longer time and with better by reducing the frequency of administration of the medication, reducing the dose, improving the patient compliances (ease of administration), by reducing the drug fluctuation level in the blood, and by enhancing the efficacy and safety of the treatment. The F7 formulation has a PS of 44.26 ± 0.84 μm, (%) EE of 76.57 ± 0.26, drug loading of 49.67% ± 0.94%, and good % CDR 94.26% ± 2.64% for an extended period of 12 hours. In addition, the candidone shows a decrease in the viability of HT 29 colon cancer cells in a dose-dependent manner. The result indicated that the prepared microsponges could release the Candidone in a sustained manner and help in the management of CRC.
Keywords: Colon cancer, microsponges, candidone, pH-sensitive polymer, cancer, Eudragit RS 100